The novel Group A Streptococcus antigen SpnA combined with bead-based immunoassay technology improves streptococcal serology for the diagnosis of acute rheumatic fever. Issue 4 (April 2018) - Hanson-Manful, Paulina; Whitcombe, Alana L.; Young, Paul G.; Atatoa Carr, Polly E.; Bell, Anita; Didsbury, Alicia; Mitchell, Edwin A.; Dunbar, P. Rod; Proft, Thomas; Moreland, Nicole J.
Highights: Streptococcal serology is crucial to the diagnosis of acute rheumatic fever. Existing serological assays suffer high background in Group A Streptococcus endemic settings. Current methods to measure anti-streptolysin-O and anti-DNaseB antibodies are incompatible so tests must be run in parallel. The novel antigen, SpnA, has improved immunokinetics for streptococcal serology compared with streptolysin-O and DnaseB. Coupling antigens to beads enables titres to three antigens to be measured simultaneously for improved efficiency. Abstract: Objectives: Streptococcal serology provides evidence of prior Group A Streptococcus (GAS) exposure, crucial to the diagnosis of acute rheumatic fever (ARF) and post-streptococcal glomerulonephritis. However, current tests, which measure anti-streptolysin-O and anti-DNaseB antibodies, are limited by false positives in GAS endemic settings, and incompatible methodology requiring the two tests to be run in parallel. The objective was to improve streptococcal serology by combining the novel GAS antigen, SpnA, with streptolysin-O and DNaseB in a contemporary, bead-based immunoassay. Methods: Recombinant streptolysin-O, DNAseB and SpnA were conjugated to polystyrene beads with unique fluorescence positions so antibody binding to all three antigens could be detected simultaneously by cytometric bead array. Multiplex assays were run on sera collected in three groups: ARF; ethnically matched healthy children; and healthy adults. Results: The ability of the antigens to detect a previous GAS exposure in ARF was assessed using the 80th centile of the healthy children group as cut-off (upper limit of normal). SpnA had the highest sensitivity at 88%, compared with 75% for streptolysin-O and 56% for DNaseB. Conclusions: SpnA has favorable immunokinetics for streptococcal serology, and can be combined with anti-streptolysin-O and anti-DNaseB in a multiplex format to improve efficiency and accuracy.